Los derechos reales en Europa - Fernández Salas, José Carlos (2014)
The study of rights in rem from an internal perspective of our national legal system is notan easy task. For that purpose, a comparativestudy of the international juridical systems canserve as both a solution and an instrument tobring forward new and innovative knowledge related to those rights.The author perceives that fundamental to notice the importance that the international character of rights in rem has acquired through time. He does, therefore, a comparative study between different rights in rem regimes in countries such as France, Germany and England. These countries are all part of the European Union, with whom Peru has signed a Free Trade Agreement.